KEKUASAAN PRESIDEN DALAM SISTEM PEMERINTAHAN INDONESIA SETELAH PERUBAHAN UNDANG-UNDANG DASAR TAHUN 1945 - , ANDRYKA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
After the constitutional amendment, Indonesia has purified the presidential system. The purification affects on the power of the president and restructuring Indonesian governance. The power of president is no longer absolute. In fact, there is limitation of president power with limitative tenure. The case of restructuring, the pattern of relation among national institutions is no longer hierarchic vertically, but functional horizontally with the principle of checks and balances. Therefore, this research was aimed to study what powers owned by the president after the change of UUD Year 1945, how the pattern of relation between the president with other power branches among the national institutions and what kind of implication resulted in relation with the use of presidential power. To answer the problem, this research used legal material in the form of decision or legal regulation and literatures about presidential power. As a legal research, the legal material is managed by using conceptual, juridical, case, historical, and comparative approaches whose implementation is appropriate with the need of this research. The result of this research showed three results. First, with constitutional amendment, there was a reduction of presidential power and control of other power branches, thus it was formed three patterns of presidential power implementation. The first is autonomous presidential power. The second is the relation between the president and national institutions is no longer hierarchic vertically presidential power needing approval of other power branches. Second, the relation between the president and other national institution is no longer hierarchic vertically with the principle of People Representativeâs supremacy as the manifestation of peopleâs unity but functional horizontally with the emphasis on the principle of checks and balances. Third, although the principle of checks and balances is applied in main national institutions, it is still possible that in the implementation of presidential power would not promote the occurrence of implication. At least, there are two implication of the usage of presidential power. The first is juridical implication and the second one is political implication.